Laccase immobilized on Au confined MXene based electrode for electrochemical detection of catechol. (2021) - Chandran, Mijun; Aswathy, E.; Shamna, I.; Vinoba, Mari; Kottappara, Revathi; Bhagiyalakshmi, Margandan
Abstract: In this study, a biosensor electrode was fabricated with Laccase (Lac) immobilized on Au/MXene over glassy carbon electrode (GCE) using the Nafion solution for the detection of catechol. As prepared Au/MXene material was characterized by XRD, SEM, and EDX. The Au nanoparticles facilitate the electron exchange between Au surface and the electro-active T1 copper site of laccase that allows the adsorbed enzymes to retain their biological electrocatalytic activity. Electrochemical oxidation of catechol with Lac/Au/MXene/GCE electrode exhibited a perfectly linear amperometric response in the catechol concentration range from 0.05 to 0.15 µM with a relatively high sensitivity of 0.05 mA/µM and a detection limit of 0.05 µM. It also displayed excellent stability, reproducibility, and repeatability. Thus, the Lac/Au/MXene/GCE biosensor excellent system for detecting catechol in industrial effluents and water-bodies to minimize environmental pollution.